A Literature Study on Cultural Digitalization in Efforts to Enhance Product Value and National Image in the Creative Industry - Leho, Osin Marjelina; Widiastini, Ni Made Ary; Yulianthini, Ni Nyoman (Dinasti International Journal of Economics, Finance & Accounting, 2026)
The study ains to examine how cultural digitalization is implemented within the creative industry sector and whether it contributes to enhancing product value and national image. This research employs a literature review method by analyzing 34 relevant articles obtained from Google Scholar, DOAJ, SINTA portal, and other academic scientific databases using the keywords “cultural digitalization,” “digital transformation,” “creative industry,” “national image,” and “product value.” Although numerous studies have discussed cultural digitalization within the creative industry context, a significant gap remains. Specifically, there is no clearly integrated model that systematically links the stages of cultural digitalization to improvements in product value and national image. Therefore, this study proposes an integrated model approach consisting of five stages of cultural digitalization: digital data collection, cultural adaptation into digital platforms, creative marketing strategies, global self-image positioning strategies, and sustainable digital transformation. The findings suggest that integrating these stages into a comprehensive framework connects previous research outcomes, particularly in explaining the relationship between digital transformation, product value enhancement, and national image development. Future research is expected to further develop a sustainable cultural digitalization implementation model and conduct empirical analyses across creative industry subsectors to strengthen economic value and national image.